2009
DOI: 10.1039/b905039f
|View full text |Cite
|
Sign up to set email alerts
|

Selective sensor utilizing a thin monolayer of b-oriented silicalite-1 crystals–magneto-elastic ribbon assembly

Abstract: This report presents the development of new selective gas sensors utilizing a b-oriented silicalite-1 layer-magneto-elastic ribbon assembly. The key principle for the operation of these sensors is monitoring the changes in the resonance frequency of the Metglas Ò strip in relation to the concentration of a component in the gas phase. This technique provides a simple way for monitoring the effects of the amount of adsorbed gases in the silicalite-1 coating. The thickness of the zeolite layer is that of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…
The fabrication of MFI zeolite films with particular b-axis orientation is especially fascinating.Unlike the conventional alkaline or hydrofluoric acid (HF) assisted neutral synthesis route,h ere we develop an ovel neutral synthesis solution system of TPABr/fumed silica/H 2 Owithout the use of HF and successfully synthesize highly b-oriented MFI zeolite films on glass-plate substrates by secondary growth. The localized weak alkaline environment created by the dissolved Na 2 Os pecies from the substrate is identified as the key factor for the depolymerization of fumed silica and subsequently the in-plane growth of zeolite seed layers.C ontinuous b-oriented MFI films can also be synthesized on other substrates in the presence of ag lass plate or at race amount of NaOH, which making our neutral synthesis route promising for the direct synthesis of MFI zeolite films and membranes on various substrates.MFI zeolite films and membranes have found many applications in the field of separation, [1][2][3][4][5][6][7][8] catalysis, [9,10] sensors, [11,12] and corrosion protection. [13,14] One particularly interestingb ut challenging issue is the fabrication of dominantly b-oriented pure silica MFI zeolite films.In2001, Wang et al for the first time reported that the delicate manipulation of the composition of the synthesis solution produced continuous b-oriented MFI thin films by in situ crystallization.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
The fabrication of MFI zeolite films with particular b-axis orientation is especially fascinating.Unlike the conventional alkaline or hydrofluoric acid (HF) assisted neutral synthesis route,h ere we develop an ovel neutral synthesis solution system of TPABr/fumed silica/H 2 Owithout the use of HF and successfully synthesize highly b-oriented MFI zeolite films on glass-plate substrates by secondary growth. The localized weak alkaline environment created by the dissolved Na 2 Os pecies from the substrate is identified as the key factor for the depolymerization of fumed silica and subsequently the in-plane growth of zeolite seed layers.C ontinuous b-oriented MFI films can also be synthesized on other substrates in the presence of ag lass plate or at race amount of NaOH, which making our neutral synthesis route promising for the direct synthesis of MFI zeolite films and membranes on various substrates.MFI zeolite films and membranes have found many applications in the field of separation, [1][2][3][4][5][6][7][8] catalysis, [9,10] sensors, [11,12] and corrosion protection. [13,14] One particularly interestingb ut challenging issue is the fabrication of dominantly b-oriented pure silica MFI zeolite films.In2001, Wang et al for the first time reported that the delicate manipulation of the composition of the synthesis solution produced continuous b-oriented MFI thin films by in situ crystallization.
…”
mentioning
confidence: 99%
“…MFI zeolite films and membranes have found many applications in the field of separation, [1][2][3][4][5][6][7][8] catalysis, [9,10] sensors, [11,12] and corrosion protection. [13,14] One particularly interestingb ut challenging issue is the fabrication of dominantly b-oriented pure silica MFI zeolite films.In2001, Wang et al for the first time reported that the delicate manipulation of the composition of the synthesis solution produced continuous b-oriented MFI thin films by in situ crystallization.…”
mentioning
confidence: 99%
“…Yan et al synthesized highly b-oriented, i.e., (0 k 0) crystal planes arranged parallel to substrate-MFI films in situ on smooth stainless steel plates by accurately manipulating the synthetic conditions [17,18]. In subsequent electrochemical testing, these films showed excellent molecular sieving properties as selective sensors [10]. Tsapatsis et al fabricated twin-free and highly b-oriented MFI membranes by secondary growth of b-oriented MFI seed monolayers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Taking Mordenite Framework Inverted (MFI) zeolite [1] (symmetry: orthorhombic; space group: P nma ; unit cell constants: a = 20.1 Ǻ , b = 19.9 Ǻ , and c = 13.4 Ǻ ) as an example, the pore system consists of straight channels (pore size: 0.53 9 0.56 nm) interconnected by zigzag channels (0.51 9 0.55 nm) [2]. In addition to their traditional uses as catalysts, adsorbents and ionic exchangers [3], zeolites can also be fabricated into thin films and used as separation membranes [4][5][6][7][8], selective sensors [9,10], low-k materials [11,12], corrosion-resistant coatings [13], and optical materials [14,15]. In the synthesis of high-quality zeolite films, the accurate manipulation and optimization of their microstructures, such as crystallographic preferred orientation (CPO), thickness, intergrowth and grain boundary structures, is critical.…”
Section: Introductionmentioning
confidence: 99%
“…7 Zeolite particles are ideal model microbuilding blocks for 2D assembly because of not only their ease in fabrication but also their inherent highly regular sub-nanometer-sized pore architectures, which may bring new features when being assembled into ordered 2D layers. In the recent years, great progress has been made in fabricating highly regular zeolite layers (unique orientation and high monolayer coverage) and their promising applications as high-performance molecular sieve membranes, [8][9][10][11][12][13][14][15] anisotropic photoluminescence generators, 16 light-harvesting systems, 17 optical devices, [18][19][20] selective sensors [21][22][23] etc. have also been extensively explored.…”
Section: Introductionmentioning
confidence: 99%